ANALISIS TINGKAT PENGETAHUAN PEMAHAMAN DAN KESADARAN PEMILIK USAHA KOS TENTANG PAJAK KOS DI KECAMATAN LOWOKWARU KOTA MALANG - Luh Dina Ekasari (OPTIMA, 2019)
Taxes are very important in increasing tax revenues in Malang City. Tax rates of types of boarding houses with a number of rooms more than 10 (ten) are set at 5% (five percent). Increased tax revenue is supported by knowledge, understanding, and awareness of taxes carried out by Plasya boarding owners on taxation. The purpose of this study is to find out the knowledge, understanding and reflection of boarding house business owners about boarding tax in Malang Lowokwaru Salvation as a whole. The research conducted is research using quantitative methods. Determination of this research sample using the pruposive sampling method. The sample was obtained as many as 40 Kos Taxpayers in Lowokwaru District, Malang City. The data used are questionnaires and documentation. The data analysis method used is multiple linear regression using the SPSS program. The results of the study prove that partially (each) knowledge of the boarding tax amounted to (3.132), the tax on the boarding tax amounted to (2.817) and awareness of the boarding tax amounted to (3.623). Overall knowledge, understanding and awareness of boarding taxes on business owners in Lowokwaru District, Malang City is 61.2%. What needs to be done by Kos Taxpayers is that it is appropriate to pay taxes such as timely taxes to increase and increase tax returns to improve the development and economy of Indonesia.